Artificial Intelligence Computer Weapon Based True Research on Corona Virus [Covid-19] - Hariom .J. Arora, Pradeep Hariom Arora (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Electronic torture, Electromagnetic radiation torture, or Psychotronic torture are terms used by individuals who are targeted by this wireless Synthetic telepathic technology or Direct Energy Weapon [Electromagnetic Radiation weapon].Wireless Synthetic telepathy technology or Super artificial intelligence computers Criminal operators, often actors or often government employees, agents or crime syndicates, use transmitted electromagnetic radiation (Such as microwave listening effects), satellite technology and surveillance techniques.Wireless Remote Neural Monitoring:  Bridging the gap between brain and technology In the field of neuroscience and technological advancement, the concept of deep tech satellite wireless neural monitoring technology has emerged as an unprecedented innovation weapon.Which has been developed to read and understand the human brain and to interact with the human brain and understand the human body, it is also a wireless direct energy weapon.These deep tech satellite surveillance criminal operators are using this Neurotechnology and wireless Direct Energy Weapons on a large scale against civilians.This true research has been done to protect citizens from illegal deep tech satellite surveillance weapon technology and cyber terrorism.The researcher has presented his research to the whole world in very simple words and in an easy manner.So that the world can easily understand this research and the governments of the countries of the world can protect their citizens from future man-made diseases and viruses.
Keywords: Remote Neural Monitoring; Direct Energy Weapon; Synthetic Telepathy Technology; Mind Control Technology; Voice to Skull [V 2 K]